The Young people's encyclopedia of the United States / Vol 1; Abernathy/Folsom Culture - Shapiro, William E. (Brookfield, Conn. : Millbrook Press, 1992)
A multivolume encyclopedia with over 1200 alphabetically-arranged entries covering such topics as the history, physical features, festivals, and music of the United States and its neighbors, Mexico and Canada
Includes index.
Keywords: Juvenile; Juvenile; United States -- Encyclopedias; North America -- Encyclopedias